Pengelolaan Sampah Dalam Pengembangan Pariwisata Berkelanjutan Di Destinasi Super Prioritas - Kek Mandalika - HAFIFI, M KADRAN (Politeknik Pariwisata Medan, 2024)
Since 2015, the central government has designated Mandalika as a Special Economic Zone (SEZ) for Tourism in Indonesia to develop the tourism sector in the West Nusa Tenggara Province (NTB). Mandalika SEZ covers an area of 1,035 hectares with high potential for beach tourism. However, waste management has become a significant challenge threatening the sustainability of tourism in this area. This study evaluates the waste management issues in Mandalika, especially during major events like MotoGP, and offers solutions through stakeholder collaboration. The methodology employed includes observation, interviews, and Focus Group Discussion (FGD) with various stakeholders. The results indicate the need for stricter regulations, improved waste management facilities, and active participation from both the local community and tourists in maintaining environmental cleanliness.